2008
DOI: 10.1270/jsbbs.58.453
|View full text |Cite
|
Sign up to set email alerts
|

Detecting QTLs for plant architecture traits in cucumber (Cucumis sativus L.)

Abstract: To improve the efficiency of breeding cucumber in China, we previously mapped QTL for most fruit-and flower-related traits of this species. Here, we mapped QTLs for six plant architecture traits including lateral branch number (LBN), lateral branch total length (LBTL), main-stem length (MSL), internode length (INL), main-stem diameter (MSD), and petiole length (PL) were detected in greenhouse environments. In total, 14 QTLs were identified for the six traits (LBN, 3; LBTL, 2; MSL, 3; INL, 2; MSD, 2; and PL, 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There is only one QTL for cucumber stem diameter that has been reported. Li [ 10 ] detected two QTLs related to cucumber stem diameter, qMSD-1 (Chr.1: 630,399 bp) on chromosome 1 between markers OP-V20 and CSFR12, and qMSD-7 (Chr.7: 20,536,944 bp) on chromosome 7 between markers e23M15a and e23M15b. The QTL on Chr.1, qMSD-1 , was far from the gSD1.1 locus (physical position 15,337,811 bp) detected on Chr.1 in this study, suggesting that the eight loci we detected are all novel loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only one QTL for cucumber stem diameter that has been reported. Li [ 10 ] detected two QTLs related to cucumber stem diameter, qMSD-1 (Chr.1: 630,399 bp) on chromosome 1 between markers OP-V20 and CSFR12, and qMSD-7 (Chr.7: 20,536,944 bp) on chromosome 7 between markers e23M15a and e23M15b. The QTL on Chr.1, qMSD-1 , was far from the gSD1.1 locus (physical position 15,337,811 bp) detected on Chr.1 in this study, suggesting that the eight loci we detected are all novel loci.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are few studies on the inheritance and gene mapping of stem diameter in cucumber. Li [ 10 ] used the F 2:3 populations constructed by S94 (North China type) and S06 (European greenhouse type) as parents to map the QTLs of the cucumber stem diameter, and detected two loci— qMSD-1 and qMSD-7 , with a heritability of 8.5%. It is difficult to develop molecular markers closely linked with stem diameter that can be used for molecular-assisted breeding.…”
Section: Introductionmentioning
confidence: 99%
“…development, cyclin, transcript factor and phytohormone pathways responsible for cell organization (Pierre-Jerome et al, 2018). In cucurbit crops, the research on stem diameter has been mainly focused on genetic analysis and QTL mapping (Li et al, 2008;Rao et al, 2021), and there is no relevant study in Luffa. In present study, we identified a significant qID2 associated with main stem internode diameter on chromosome 9, which explained 11% of the phenotypic variation (Figure 2; Supplementary Table S6).…”
Section: Laccrwn3 Regulating the Internode Diameter Variation Of Luffamentioning
confidence: 99%
“…The software also provides the potentially superior QTL design for improving complex traits using the main QTL effects and the QTL × environments interaction effects [28]. Because of the advantages of using MCIM to analyze digenic epistasis and QTL × environment interactions, and the user-friendly software that is now available, the MCIM approach has been widely applied to the analyses of the QTLs for complex traits in various plant experimental populations such as wheat [29][30][31][32][33][34], barley [35], soybean [36][37][38][39], cucumber [40], cabbage [41], cotton [42], rapeseed [43,44] and rice [45][46][47][48], as well as in Drosophila [49].…”
Section: Qtl Mappingmentioning
confidence: 99%